2016
DOI: 10.1186/s12891-016-1080-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work related physical activity and leisure physical activity on the risk and prognosis of neck pain – a population based cohort study on workers

Abstract: BackgroundThe effect of physical activity on risk and prognosis for neck pain has been studied earlier with inconclusive results. There is a need for large prospective studies on the subject. The aim of this study was to investigate if work related physical activity and physical activity during leisure time are of importance for the risk and prognosis of neck pain in men and women.MethodsWe used the Stockholm Public Health Cohort and formed two sub-cohorts of the working population based on data from 2002. Coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
1
22
0
1
Order By: Relevance
“…In adulthood, overall participation in PA, compared to physical inactivity, has indicated favorable associations with both LBP and NSP (Landmark et al, 2013; Palmlof et al, 2016; Shiri and Falah-Hassani, 2017), whereas participation in vigorous activities has been related to unfavorable outcomes (Heneweer et al, 2011). While the relationship of PA level with LBP and NSP has remained debatable at the population level (Sitthipornvorakul et al, 2011), it has also been suggested that instead of PA level, the improved physical fitness, both aerobic and muscular, could be beneficial in the prevention of LBP (Heneweer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In adulthood, overall participation in PA, compared to physical inactivity, has indicated favorable associations with both LBP and NSP (Landmark et al, 2013; Palmlof et al, 2016; Shiri and Falah-Hassani, 2017), whereas participation in vigorous activities has been related to unfavorable outcomes (Heneweer et al, 2011). While the relationship of PA level with LBP and NSP has remained debatable at the population level (Sitthipornvorakul et al, 2011), it has also been suggested that instead of PA level, the improved physical fitness, both aerobic and muscular, could be beneficial in the prevention of LBP (Heneweer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies collected clinical characteristics, physical status, and psychological factors as potential predictive factors. [ 26 , 27 ] However, to our knowledge, few studies have focused on radiological features, especially MCs. The incidence of MCs in the lumbar spine is significantly higher than in the cervical spine, resulting in a focus in most of the literature on MCs on the lumbar spine, with few studies reporting on the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our group have explored the role of physical activity in the risk 25 and recovery of NP and back pain, 26 , 27 suggesting it as having a protective effect in women. Similarly, previous studies on the effect of smoking and alcohol consumption on sick leave due to unspecific LBP or NP showed that the former is associated with an increased risk and the latter suggested neither an association nor a protective effect.…”
Section: Introductionmentioning
confidence: 99%